Hip arthroscopy in osteoarthritis consequent to FAI - Dall'Oca, Carlo; Trivellin, Giacomo; D'Orazio, Luca; Sambugaro, Elena; Mezzari, Silvio; Zanetti, Gabriele; Corbo, Valentina Rita; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2016)
Background: Femoral Acetabular Impingement (FAI) means a set of alterations involving the acetabulum, proximal femur, or both of these components that can results in osteoarthritis. Arthroscopy is a choice for the treatment of initial stages of osteoarthritis (OA) in order to reduce evolution of the degenerative processes; advanced degrees of osteoarthritis are absolute contraindications. Materials and Methods: 40 patients affected by osteoarthritis in FAI  underwent hip arthroscopy between May 2010 and March 2015. In all 40 cases OA secondary to FAI was diagnosed. All patients were clinically and instrumentally analyzed pre-operatively and then post-operatively after 3, 6, and 12 months. We evaluated the degree of OA using the Tonnis classification; our study included only patients affected by Tonnis grade 0-2 osteoarthritis. Results: The mean modified Harris Hip Score showed an evolution from 54.7 points to an average value of 89,1 points after 12 months. The Lower Extremities Functional Scale evolved by 43 points to an average value of 65,28 points. Conclusions: Based on the data of this study, supported by the concordance with recent literature reviews, in degrees Tonnis 0 and 1 an arthroscopic treatment is recommended. Instead the therapeutic algorithm in Tonnis grade 2 is still being discussed. We detect a significant response to arthroscopic intervention which leads us to suggest that validation of this method needs further confirmatory studies.